ANALYSIS OF FACTORS INFLUENCING COMMUNITIES TO CHOOSE A SHARIA PEER TO PEER LENDING PLATFORM - Pitri Yandri; Muhammad Sarbini (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The purpose of this research is to analyze the factors that influence people to choose sharia peer to peer lending. The independent variables in this study are interest, trust, and product knowledge, while the dependent variable is sharia peer to peer lending. Data collection was carried out by distributing questionnaires using Google forms. This research study was conducted on employees who have offices in Jabodetabek and previously or currently still have investments. The data analysis technique used is Structural Equational Modeling (SEM). The results showed that interest and trust variables had a significant effect on people's decisions to choose sharia peer to peer lending. However, the product knowledge variable has no significant effect on people's decisions to choose sharia peer to peer lending. This research is useful for lenders and sharia peer to peer lending companies in particular to be able to improve their company's performance in order to achieve company goals.